Brand Ambassador dan Konten Instagram sebagai Faktor Pembentuk Brand Image Y.O.U - Assya Putri Sanggita; Oktaviana Purnamasari (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
The current increasingly fierce business competition, coupled with the emergence of new businesses, has prompted businesspeople to seek ways to dominate and maintain their market share, including in the skincare and cosmetics business. The purpose of this study is to identify brand ambassadors, to identify Instagram content, to identify brand image, to partially measure the influence of Kim Soo Hyun as a brand ambassador on brand image, to partially measure the influence of Instagram content on brand image, and to simultaneously measure the influence of brand ambassadors and Instagram content on brand image. The theory used for variable X1 is brand ambassador with the dimensions of visibility, credibility, attractiveness, and power. X2 is Instagram content with the dimensions of credible, shareable, useful or fun, interesting, relevant, different, and on brand. Variable Y is brand image with the dimensions of brand identity, brand personality, brand association, brand attitude, and behavior. This study uses a quantitative approach with a survey method. The data collection technique uses a questionnaire distributed to 135 respondents who are followers of the @youbeauty_idn account. The data analysis technique used was multiple linear regression. The sampling technique used was simple random sampling. The results of this study showed that the partial effect of X1 on Y was 44.7%, the partial effect of X2 on Y was 70.5%, and the simultaneous effect of X1 and X2 on Y was 71.8%, with the remaining 28.2% being influenced by factors outside the variables.